Two new species of Psephenops Grouvelle from Belize (Coleoptera: Byrrhoidea: Psephenidae), with a key to the known species from Mexico and Central America - Arce-Pérez, Roberto; Novelo-Gutiérrez, Rodolfo (Zootaxa, 2013)
Two new species, Psephenops spiniparameri sp. nov. and P. shepardi sp. nov. are described, based on specimens collected from Cayo and Toledo Districts in Belize, bringing the total number of described species assigned to the genus to ten.